Estudos sobre a síntese de derivados do tipo benzoclorinas - Souza, Juliana Maria de (2016)
Herein, studies about the synthesis of new benzochlorin derivatives were carried out aiming at the preparation of compounds with special photophysical properties, such absorption bands between the visible and near infrared region. The main synthetic approach was planned to start from the formylated pyrrole (i) in order to obtain the compound (ii) as a precursor for the synthesis of chlorins. Subsequent oxidation was also planned to give the corresponding benzochlorins (iii) (Scheme iv)... continua no texto